An elderly female patient with ROS1 rearrangement primary lung adenocarcinoma and breast carcinoma: a rare case report and review of the literature. Issue 3 (28th August 2019) - Yang, Xiaojuan; Qin, Diyuan; Zhang, Yu; Li, Xue; Liu, Ning; Zhou, Ying; Feng, Ming; Wang, Yongsheng
Abstract: We report the case of a 90-year-old female patient who was suffering from c-ros oncogene 1 ( ros-1 ) rearrangement adenocarcinoma and breast cancer. After about 14 months of a reduced dose of crizotinib treatment, she had a stable disease according to the Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1). This patient's case demonstrates that ros-1 rearrangements are not limited to patients of young age. In addition, this case indicates that crizotinib, as second-line, or even first-line, treatment may be effective and manageable in elderly patients. Furthermore, for elderly patients carrying a ros1 fusion, a reduced dose of crizotinib may be efficacious rather than a resistance factor. Based on our findings, we recommend that elderly patients with advanced lung adenocarcinoma should be considered for inclusion in molecular screening for ros-1 translocation, especially for never-smokers negative for epidermal growth factor receptor ( egfr ) mutation and the fusion between echinoderm microtubule associated protein-like 4 (EML4) and anaplastic lymphoma kinase (ALK). This deserves attention because the population is aging, with increasing incidence and morbidity of multiple primary malignant tumors. Neglect of breast nodules at the onset is one of the limitations of our case, as combination of primary lung cancer with breast cancer is common. Above all, use of antiestrogens before and after the diagnosis of non-small-cell lung cancer is related to a reduced risk of lung cancer mortality. Therefore, careful attention should always be paid to these cases.